2016
DOI: 10.1016/j.marenvres.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene profiling of planktonic and biofilm microbial populations in the Gulf of Guinea using Illumina NGS

Abstract: 16S rRNA gene profiling using a pipeline involving the Greengenes database revealed that bacterial populations in innermost (proximal to the steel surface) and outer regions of biofilms on carbon steel exposed 3 m below the surface at an offshore site in the Gulf of Guinea differed from one another and from seawater. There was a preponderance of gammaproteobacterial sequences, representing organisms known for hydrocarbon degradation. Total DNA from the innermost layer was 1500 times that recovered from the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 46 publications
5
16
2
Order By: Relevance
“…Some differences, however, were also observed with Bacteroidetes distributions, for example, being high in seawater through to lowest in the tubercle inner layer in our study (Fig. 4), but the opposite being reported in (22).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Some differences, however, were also observed with Bacteroidetes distributions, for example, being high in seawater through to lowest in the tubercle inner layer in our study (Fig. 4), but the opposite being reported in (22).…”
Section: Discussioncontrasting
confidence: 74%
“…There were some similarities between our bacterial findings and a third MIC study (Zhang 2019), particularly with similar abundances of Proteobacteria and Bacteroidetes. In general, other studies have reported more Firmicutes (X. Li et al (21), S. Celikkol-Aydin et al (22) – mostly Defulfotomaculum ) and sometimes more Actinobacteria (22, 23), compared to our results, but the Proteobacteria and Bacteroidetes are abundant phyla in all these studies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This difference between the medium and the biofilm in terms of microbial flora might reflect a real dissociation between the composition of the medium and the composition of the biofilm at the surface of the material (Figure 3, Figure 4). Celikkol-Aydin et al [51] characterized a marine biofilm dominated by the phyla Cyanobacteria, Bacteroidetes and Proteobacteria while the seawater in which it was formed was dominated by the phyla firmicutes and proteobacteria [51]. In this study, the steel surface was a favourable environment for the enrichment of Cyanobacteria and Bacteroidetes.…”
Section: Heterogeneity Between the Planktonic Bacterial Populations (mentioning
confidence: 72%
“…At the same time, the development of biological characterization tools in the past few years has provided important insights into specific marine bacterial groups and their significance in biocorrosion under controlled laboratory conditions [32][33][34][35]. More recent studies based on complete community approaches have finally revealed the complexity of real microbial systems and paved the way for a more systematic understanding of the biocorrosion phenomenon [36][37][38][39][40]. The current understanding is that biocorrosion associated with biofilm formation and growth in natural environments is a complex process; the nonlinearity of this process is determined by numerous factors, of both the abiotic and biotic types.…”
Section: Introductionmentioning
confidence: 99%